A systematic review of the proteomic profile of in vivo acquired enamel pellicle on permanent teeth. (October 2021) - Hu, Hongying; Burrow, Michael Francis; Leung, Wai Keung
Highlights: Acquired pellicle plays important role in the maintenance of oral health. So far there is no consensus in terms of reference standards of acquired pellicle proteome. This report provided, for the first time, a comprehensive review on the proteomic profile of in vivo acquired enamel pellicle (AEP), with emphasis on the complete set of proteins identified in systemically and dentally healthy adults. An updated in vivo AEP proteome with fifteen "core in vivo 2-h AEP proteins" was identified. The information generated is essential for the further studies. Abstract: Objectives: To provide a comprehensive review on the proteomic profile of in vivo acquired enamel pellicle (AEP) formed on permanent teeth. Data/sources: PubMed, EMBASE (Ovid) and Web of Science databases were searched for eligible studies (up to December 2020). Studies reporting mass spectrometry-based proteomic analysis of in vivo AEP were included. Risk of bias assessment was performed. Qualitative and quantitative proteomic data were extracted, integrated, then followed by bioinformatic analysis. Study selection: Eleven studies were included, involving 122 systemically and dentally healthy adults from four different research groups. Pooled AEP samples from study participants were the normal practice for all included studies. A total of 257/93/108/870 non-redundant proteins were detectable from the in vivo ≤ 5 min/10-min/60-min/2-h AEP samples, respectively. Fifteen "core in vivo 2-h AEP proteins", generally associated with immune and/or inflammatory responses, were consistently identifiable from all four research groups. Eight included studies conducted relative quantitative proteomic analysis, while no statistical analysis could be undertaken due to the inherent limitation of the relative quantification in the proteomics analyses of these studies. Conclusions: A systematic review on adult in vivo AEP proteomic profile was undertaken. The results provide a comprehensive appreciation of the AEP proteome in healthy individuals from in vivo sampling. Further studies are warranted to clarify the biological role of AEP on oral health, particularly at an individual level. Clinical significance: A comprehensive appreciation of the proteomic profile of in vivo AEP in healthy individuals is essential to further understand its functions in oral health and disease. The information generated also provides insights for future studies. Graphical abstract: Image, graphical abstract